The Influence of Quality of Service and Goods’ Delivery Punctuality an Customer Satisfaction With Customer Trust as an Intervening Variable - Ardiansyah; Slamet Ahmadi (Syntax Idea)
Panasonic Industrial Components Indonesia is a subsidiary of the Panasonic Group which is a global electronics company that has subsidiaries in many countries that provide import and export services in the field of electronic components. With this increasingly existing competition, companies are expected to be able to know the factors that can affect customer satisfaction including service quality, delivery punctuality, customer trust and customer satisfaction. Based on the phenomenon above, the authors are interested in taking the title of research on the effect of service quality and punctuality delivery on customer satisfaction with trust as an intervening variable. The purpose of this study was to determine the effect of service quality and delivery of goods on customer satisfaction and trust as intervening variables Research conducted at PT. Panasonic Industrial Components Indonesia, with a study population of 171 customers, spread across 12 countries using the slovin formula to obtain a sample of 120 respondents at a 5% margin of error. for collecting data using the technique of questionnaire methods, and direct observation. And for data analysis using the Smart Partial Least Square (PLS) analysis method version 3.0, the data tests used in this study are reliability tests, validity tests, statistical tests and classical assumption tests. The results showed H1: There is a positive effect of service quality on customer satisfaction, H2: There is a positive effect on timely delivery on customer satisfaction, H3: There is a positive effect of service quality on trust 0.185, 0.191, 0.088, 2.112, 0.035, H4: There is a positive influence on time delivery on Trust 0.042, 0.023, 0.105, 0.402, 0.688, H5: There is a positive effect of trust on customer satisfaction 0.164, 1.993, 0.047, The hypothesis is accepted, H6: There is an indirect effect of service quality on customer satisfaction through trust 0.030, 0.034, 0.025, 1.232, 0.218, H7: There is an indirect effect of timely delivery on customer satisfaction through trust.